Contract research, the university, and the academic - Crawshaw, Bruce (Kluwer Academic Publishers, 1985)
With the decline in the funding of university research activities from traditional sources, many universities are instigating contract research programs as a means of funding research. This article examines some of the implications of university-based contract research, drawing largely on the author's own experiences. The problems which are examined include the moral and ethical implications, the legal aspects, problems over ownership of research results, the implications for staff rights, the status of contract researchers, the implications for publication, problems of authority, responsibility and social justice, and the conflicts between teaching and research. The article concludes with eleven points for successful university-based contract research. © 1985 Elsevier Science Publishers B.V.